Positive Politeness Strategies Used by the Character in the Movie “The Patriot” - Rainna Wati, Ni Luh Hani; Made Puspani, Ida Ayu (Humanis; Vol 24 No 1 (2020), 2020)
The aims of this study is to figure out the used of politeness strategy uttered by the character in The Patriot movie and the influence of gender to the level of politeness within the movie . Documentation method and note-taking technique were applied in collecting the data of this study. The data were obtained from the movie The Patriot, furthermore, the data were classified based on their types of politeness and also based on the speaker’s gender and analysed qualitatively using the theory of Politeness proposed by Brown and Levinson (1978) and the theory of sociolinguistics proposed by Ronald Wardhaugh (2010). The analysis revealed that the character in the movie The Patriot applied eleven out of fifteen strategies proposed by Brown and Levinson. Regarding to the gender of the character, women consistently tend to use neutral style when they have conversation s both with women or men. On the other hand, men are using various level s of formality when they have conversation.